A New Proof for the Description of Holomorphic Flows on Multiply Connected Domains - F. Jafari; Z. Słodkowski; T. Tonev (International Journal of Mathematics and Mathematical Sciences)
We provide a new proof for the description of holomorphic and biholomorphic flows on multiply connected domains in the complex plane. In contrast to the original proof of Heins (1941) we do this by the means of operator theory and by utilizing the techniques of universal coverings of the underlying domains of holomorphic flows and their liftings on the corresponding universal coverings.